Aplikasi Metode Volumetrik dalam Estimasi Potensi Panas Bumi Berdasarkan Parameter Fisis Reservoir (Studi Kasus Daerah Panas Bumi “Z”) - Latifah Nurul Qomariyatuzzamzami; Zuhdiyah Matienatul Iemaaniah; Alamta Singarimbun (Universitas Sultan Ageng Tirtayasa, 2023)
Geothermal is a renewable energy strategically developed in Indonesia, but its utilization has not been maximized. Geothermal exploration requires high costs, so estimating energy reserves in potential areas is essential. This study was conducted to determine the electrical energy potential of geothermal area